2012
DOI: 10.1016/j.jff.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Anti-invasion and apoptosis induction of chlorella (Chlorella sorokiniana) in Hep G2 human hepatocellular carcinoma cells

Abstract: Apoptosis Invasion Human hepatocellular carcinoma cells Hep G2 cells A B S T R A C T The effects of 80% ethanolic extract derived from commercial granule chlorella (GPE) on cell viability, invasion capacity and apoptosis in human hepatoma cell line (Hep G2 cells) were investigated. The results demonstrated that GPE decreased cell viability, induced apoptosis and showed invasion inhibitory effects in the Hep G2 cells. GPE-triggered apoptosis was confirmed by 4 0 -6-diamidino-2-phenyindole (DAPI) staining and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…53) Other studies also demonstrated that antioxidant activities reduced MMP expression and tumor invasion. [54][55][56] Based on these reports, it is likely that antioxidants in UE could greatly suppress PI3K/Akt signaling and prevent prostate cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…53) Other studies also demonstrated that antioxidant activities reduced MMP expression and tumor invasion. [54][55][56] Based on these reports, it is likely that antioxidants in UE could greatly suppress PI3K/Akt signaling and prevent prostate cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…HSC‐3 cells were incubated with various concentrations of CC‐EO or trans ‐cinnamaldehyde for 48 h. For the DNA fragmentation assay, isolated DNA was separated using gel electrophoresis and was stained using ethidium bromide before the photographs were obtained under UV light (Chou et al, ). For DAPI staining, the cells were washed using PBS, were stained using DAPI and were subsequently photographed as described in our previous study (Chung et al, ). For the comet assay, the cells were harvested, DNA was isolated and electrophoresis was performed according to a previously described method (Chung et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For DAPI staining, the cells were washed using PBS, were stained using DAPI and were subsequently photographed as described in our previous study (Chung et al, ). For the comet assay, the cells were harvested, DNA was isolated and electrophoresis was performed according to a previously described method (Chung et al, ). DNA damage in HSC‐3 cells was quantified as the tail moment (the DNA product in the tail and the mean migration distance in the tail).…”
Section: Methodsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) such as nitric oxide, superoxide anion, hydrogen peroxide, peroxynitrite and hydroxyl radical, is well known to act as important mediators of apoptotic cell death or/and cell cycle progression (Chung et al, 2012;Park, Han, Kim, & Kim, 2007). ROS could trigger DNA damage to activate the p53 pathway (Wiseman, 2006).…”
Section: Nb Enhances Dcur-induced G2/m Phase Arrest Through Ros-mediamentioning
confidence: 99%